1999
DOI: 10.1049/el:19990222
|View full text |Cite
|
Sign up to set email alerts
|

Non-contacting holographic surface acoustic wave microscope

Abstract: A non-contacting laser-based surface acoustic wave microscope is described, which overcomes the problem normally associated with non-contacting acoustic microscopy, namely the poor signal to noise ratio. The solution enables the scan rate to be increased dramatically. Details of the optical system and associated electronics are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
2000
2000

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In previous publications we have shown that this allows one to detect the ultrasonic distribution without averaging. 6,9 We have also shown how the increase in surface wave amplitude allows fast analog electronics to be used rather than a digital storage oscilloscope; this greatly improves the rate of image acquisition obtained in a noncontacting surface wave acoustic microscope. 9 The light distributions on the sample were obtained using a CGH, which produced a single arc.…”
Section: A Saw Focusingmentioning
confidence: 97%
See 2 more Smart Citations
“…In previous publications we have shown that this allows one to detect the ultrasonic distribution without averaging. 6,9 We have also shown how the increase in surface wave amplitude allows fast analog electronics to be used rather than a digital storage oscilloscope; this greatly improves the rate of image acquisition obtained in a noncontacting surface wave acoustic microscope. 9 The light distributions on the sample were obtained using a CGH, which produced a single arc.…”
Section: A Saw Focusingmentioning
confidence: 97%
“…6,9 We have also shown how the increase in surface wave amplitude allows fast analog electronics to be used rather than a digital storage oscilloscope; this greatly improves the rate of image acquisition obtained in a noncontacting surface wave acoustic microscope. 9 The light distributions on the sample were obtained using a CGH, which produced a single arc. This provided focusing of the laser-generated surface waves, but offered little control of the frequency content of the resulting surface wave distribution.…”
Section: A Saw Focusingmentioning
confidence: 97%
See 1 more Smart Citation
“…6 To increase the amplitude of photoacoustic signal several schemes with focusing of the acoustic waves have been proposed. 7,8 The insufficient spatial resolution of conventional ultrasound detection methods can be improved up to nanoscale by using the scanning probe methods ͑SXM͒. SXM measurements have atomic spatial resolution and high sensitivity to surface displacement, but in general a low frequency response range ͑tens of kHz͒, which prevent direct measure-ments of fast ultrasonic waves and pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction: There is no doubt that laser ultrasonics will become even more important and used more routinely in non-destructive testing in the next decade. In an earlier Letter [1] we showed how a non-contacting surface acoustic wave microscope could be produced by combining fast analogue detection electronics with a computer-generated hologram to produce an optical distribution, which acts as a source for focused surface waves. We demonstrated similar imaging performance to that of a fluid coupled acoustic microscope.…”
mentioning
confidence: 99%